Doing science in futureless times: War, political engagement, and national mission in croatian ethnology during the 1990s - Cosovschi, Agustín (2019)
From a perspective rooted in intellectual and cultural history, the author accounts for the profound disciplinary transformations undergone by ethnology as practised at the Institute of Ethnology and Folklore Research (IEF) in Zagreb, Croatia, during the early 1990s. In a context shaped by the Yugoslav breakup and the outbreak of war, and also as a result of theoretical transformations that had taken place in Croatian ethnology during the previous decade, many researchers at this institute undertook a new ethnological practice that involved among other things the questioning of the notion of objectivity and the redefinition of the political role of the ethnologist. The author analyses these changes in terms of converging factors, namely the theoretical influences coming from American, French, and German scholarship, the disciplinary crisis caused by a self-perception of social marginality, and the radical and violent sociopolitical transformations of the early 1990s.